ANALISIS KOMENTAR PULEN DAN TOBRUT DI MEDIA SOSIAL PADA AKUN TIKTOK @spotifyid TERHADAP PENYANYI BERNADYA MELALUI PERSPEKTIF BAHASA INDONESIA - Delisha Dita Winelda; Roma Kyo Kae Saniro; Firyal Fauziah Ghina Syanmid; Aprilia Wulandari; Muhammad Fhadhillah Akbar; Aura Lovery Triazhani; Virgie Kayla Biyentami (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
Humans are social creatures, in their daily lives they are never separated from the activities of interaction between each other. The development of technology has created interactions that are increasingly widespread and do not require face-to-face meetings. One form of interaction is comments on social media. The research reviews the theme “Language Politeness” by analyzing the moral decline of Indonesian society in the use of language on social media. From this theme we examine a case that is booming on social media, namely netizen comments using the words “Tobrut” and “Pulen” on the Tiktok @spotifyid account against the young singer Bernadya. Through the Indonesian Language Perspective, this study aims to explore the word used as a development and change in the meaning of a word, as well as violations of the norms of politeness in the scope of language, decency and religion. Through a qualitative method with an observational approach, this research analyzes the meaning, context, and impact of using impolite language on social media. The results show the influence of social views on women shown in interacting on social media. That is by using a word to interact. The actions of netizen comments to Bernadya not only damage language but also morals and religion. It is hoped that this research can provide a deeper understanding of the importance of language politeness in the dig environment.